2019
DOI: 10.3390/ma12193126
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Mineralization: The Potential of Mineralomics

Abstract: Pathological mineralization has been reported countless times in the literature and is a well-known phenomenon in the medical field for its connections to a wide range of diseases, including cancer, cardiovascular, and neurodegenerative diseases. The minerals involved in calcification, however, have not been directly studied as extensively as the organic components of each of the pathologies. These have been studied in isolation and, for most of them, physicochemical properties are hitherto not fully known. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 195 publications
(200 reference statements)
0
37
0
2
Order By: Relevance
“…For the second set, containing less than 20% by weight Wk, FE-SEM was also performed for bacterial imprints to establish a possible infection process. Such a multiscale approach taking into account chemistry and morphology has already been used to develop new diagnostic tools, or to deduce the very first steps of calcification pathogenesis [54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…For the second set, containing less than 20% by weight Wk, FE-SEM was also performed for bacterial imprints to establish a possible infection process. Such a multiscale approach taking into account chemistry and morphology has already been used to develop new diagnostic tools, or to deduce the very first steps of calcification pathogenesis [54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, our results indicated that the hardened tissue at the severe stage of lymphoedema may not only be attributed to fibrosis, but also to pathologic mineralization of adipose tissues, which has not been recognized before. Pathological mineralization occurs in nearly all soft tissues and is associated with diverse human diseases such as cancer and atherosclerosis, but is sometimes overlooked (Tsolaki and Bertazzo, 2019). Our study highlights the aberrant differentiation or pathological mineralization of ASCs in lymphoedema, which may serve as a novel angle for treatment.…”
Section: Discussionmentioning
confidence: 80%
“…Исходя из того, что по стехиометрическим данным во всех минерально-фосфатных фазах, в том числе и встречаемых в окулярных тканях, весовая доля Ca превышает долю P [11], исследуемые ткани склеры и трабекулы ретроспективно были поделены на 2 группы. Образцы с доминирующей весовой долей кальция (Ca:P>1) были определены как минеральнофосфатные.…”
Section: формы накопления P в склере и трабекуле при поугunclassified